Lymph node yield less than 12 is not a poor predictor of survival in locally advanced rectal cancer after laparoscopic TME following neoadjuvant chemoradiotherapy - Yang, Hong; Xing, Jiadi; Zhang, Chenghai; Yao, Zhendan; Wu, Xiuxiu; Jiang, Beihai; Cui, Ming; Su, Xiangqian (Frontiers in Oncology, 2022)
Purpose: Previous studies have confirmed that neoadjuvant chemoradiotherapy (nCRT) may reduce the number of lymph nodes retrieved in rectal cancer. However, it is still controversial whether it is necessary to harvest at least 12 lymph nodes for locally advanced rectal cancer (LARC) patients who underwent nCRT regardless of open or laparoscopic surgery. This study was designed to evaluate the relationship between lymph node yield (LNY) and survival in LARC patients who underwent laparoscopic TME following nCRT. Methods: Patients with LARC who underwent nCRT followed by laparoscopic TME were retrospectively analyzed. The relationship between LNY and survival of patients was evaluated, and the related factors affecting LNY were explored. To further eliminate the influence of imbalance of clinicopathological features on prognosis between groups, propensity score matching was conducted. Results: A total of 257 consecutive patients were included in our study. The median number of LNY was 10 (7 to 13) in the total cohort. There were 98 (38.1%) patients with 12 or more lymph nodes harvested (LNY ≥12 group), and 159 (61.9%) patients with fewer than 12 lymph nodes retrieved (LNY <12 group). There was nearly no significant difference between the two groups in clinicopathologic characteristics and surgical outcomes except that the age of LNY <12 group was older (P<0.001), and LNY <12 group tended to have more TRG 0 cases (P<0.060). However, after matching, when 87 pairs of patients obtained, the clinicopathological features were almost balanced between the two groups. After a median follow-up of 65 (54 to 75) months, the 5-year OS was 83.9% for the LNY ≥12 group and 83.6% for the LNY <12 group (P=0.893), the 5-year DFS was 78.8% and 73.4%, respectively (P=0.621). Multivariate analysis showed that only patient age, TRG score and ypN stage were independent factors affecting the number of LNY (all P<0.05). However, no association was found between LNY and laparoscopic surgery-related factors. Conclusions: For LARC patients who underwent nCRT followed by laparoscopic TME, the number of LNY less than 12 has not been proved to be an adverse predictor for long-term survival. There was no correlation between LNY and laparoscopic surgery-related factors.